The loads developed by epicondylar and epitrochlear muscles across the elbow joint. A dynamic simulated model. (December 2022) - Pérez-Abad, Miguel; Noriego Muñoz, Diana; Ferreres Claramunt, Ángel; del Valle Jou, Montserrat; Rodríguez-Baeza, Alfonso
Abstract: The radio-humeral joint has traditionally been believed to support most of the loads transmitted through the elbow. Load transfer through the elbow has been a controversial issue since the publication of the first biomechanical studies on the subject, most of which were based on extrinsic forces acting on the extended joint. The present study analyzes load distribution across the six different compartments in the elbow while the joint is flexed, as well as the intrinsic forces generated in the epicondylar and epitrochlear muscles. Ten cadaveric elbows were positioned at 90° of flexion, forearm in a neutral position and wrist at 0°. Tekscan sensors were used for measuring intraarticular pressures. Forces generated by epitrochlear muscles results in a series of loads that affect mainly the anteromedial facet (40%), followed by the posterolateral facet (34%) of the ulnohumeral joint, with the flexor carpi ulnaris generating the heaviest loads (43% on the anteromedial and 38% on the posterolateral facets). Conversely, the forces generated by the epicondylar muscles, similar in behavior but with an opposite direction, convey heavier loads to the elbow's anterolateral facet (45%), followed by the radiohumeral joint (26%) with the extensor carpi ulnaris generating the heaviest loads (54% on the anterolateral facet and 17% on the radiohumeral joint). Our results indicate that the elbow joint exhibits a characteristic load distribution pattern that depends on the muscles, as intrinsic forces are generated by the epicondylar and epitrochlear muscles. The anterior portion of the ulnohumeral joint is the area bearing the heaviest loads.